An analysis of the movement of urban food prices in Nigeria, 1954 - 1965 - Adejunmobi, E.O. (Ibadan : Nigerian Institute of Social & Economic Research, 1970)
In this paper, a short background of study is given and the sources of data given. Methodology, analysis of data and results follow. Then a summary of results of the analysis and conclusion.
Reprinted from the Nigerian Journal of Economic and Social Studies, Vol. XII, No. 1, March 1970.
Includes bibliographical references.
osc 30/01/2019
Loans
Keywords: Food crops; Sustainable agriculture